2020
DOI: 10.1161/jaha.119.013989
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Consultation Reduces Heart Failure Transitions: A Matched Analysis

Abstract: Background Palliative care supports quality of life, symptom control, and goal setting in heart failure ( HF ) patients. Unlike hospice, palliative care does not restrict life‐prolonging therapy. This study examined the association between palliative care during hospitalization for HF on the subsequent transitions and procedures. Methods and Results Veterans admitted to hospitals with HF fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Such an individual approach, based on sensitive in-depth communication, could support or prevent invasive interventions and hospitalizations. Some interventions may not correspond with personal values and wishes, or be perceived as too burdensome ( 22 ). Such advance care planning reduces readmissions and costs and increases the satisfaction with the care received ( 16 , 23 ).…”
Section: Definition Of Palliative Carementioning
confidence: 99%
“…Such an individual approach, based on sensitive in-depth communication, could support or prevent invasive interventions and hospitalizations. Some interventions may not correspond with personal values and wishes, or be perceived as too burdensome ( 22 ). Such advance care planning reduces readmissions and costs and increases the satisfaction with the care received ( 16 , 23 ).…”
Section: Definition Of Palliative Carementioning
confidence: 99%
“…Although the studies are small, involvement of specialty palliative care has been found to reduce ICD implantations for patients whose goals of care do not align with ICD shocks. 59 For patients with existing ICDs, palliative care consultation has been found to increase ICD deactivations and improve concordance between code status and device settings. 47,48 Palliative care consultants occasionally become involved with patients with a permanent pacemaker when questions arise regarding the role of pacemaker deactivation.…”
Section: Palliative Care For Shared Decision-making In Arrhythmiasmentioning
confidence: 99%
“…Palliative care for HF patients can be complex, but may result in improved quality-of-life as well as fewer readmissions and a reduction of invasive treatment (e.g. rates of mechanical ventilation) 12 .…”
Section: Disclosures: Nonementioning
confidence: 99%